Biofortification of Cereals With Foliar Selenium and Iodine Could Reduce Hypothyroidism - Lyons, Graham (Frontiers in Plant Science, 2018)
Concurrent selenium and iodine deficiencies are widespread, in both developing and developed countries. Salt iodization is insufficient to ensure global iodine adequacy, with an estimated one-third of humanity at risk of hypothyroidism and associated iodine deficiency disorders (IDD). Agronomic biofortification of food crops, especially staples such as cereals, which are consumed widely, may be an effective component of a food system strategy to reduce selenium and iodine malnutrition. Iodine and selenium are needed in the optimum intake range for thyroid health, hence joint biofortification makes sense for areas deficient in both. Foliar application is recommended as the most effective, efficient, least wasteful method for selenium and iodine biofortification. Currently, selenium is easier to increase in grain, fruit and storage roots by this method, being more phloem mobile than iodine. Nevertheless, strategic timing (around heading is usually best), use of surfactants and co-application with potassium nitrate can increase the effectiveness of foliar iodine biofortification. More research is needed on iodine transporters and iodine volatilization in plants, bioavailability of iodine in biofortified plant products, and roles for nano selenium and iodine in biofortification. For adoption, farmers need an incentive such as access to a premium functional food market, a subsidy or increased grain yield resulting from possible synergies with co-applied fertilizers, enhancers, fungicides andor insecticides. Further research is needed to inform these aspects of foliar agronomic biofortification.